Palladium‐Catalyzed Regioselective Allylation of Chloromethyl(hetero)arenes with Allyl Pinacolborate. Issue 16 (19th May 2017) - Zhang, Sheng; Ullah, Aziz; Yamamoto, Yoshinori; Bao, Ming
Abstract: The palladium‐catalyzed regioselective allylation reaction between chloromethyl(hetero)arenes and allyl pinacolborate is reported in this work. Chloromethylarenes smoothly reacted with allyl pinacolborate, producing para ‐allylated dearomatization products or para ‐allylated arenes in satisfactory to good yields. 2‐(Chloromethyl)thiophenes and 2‐(chloromethyl)furans bearing substituents on the 5‐positions also smoothly reacted with allyl pinacolborate, producing the 5‐allylated dearomatization products in satisfactory yields. Abstract :